2017
DOI: 10.5487/tr.2017.33.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Xylene Induces Oxidative Stress and Mitochondria Damage in Isolated Human Lymphocytes

Abstract: Xylene is a cyclic hydrocarbon and an environmental pollutant. It is also used in medical technology, paints, dyes, polishes and in many industries as a solvent; therefore, an understanding of the interaction between xylene and human lymphocytes is of significant interest. Biochemical assessment was used to demonstrate that exposure of lymphocytes to xylene induces cytotoxicity (at 6 hr), generates intracellular reactive oxygen species, collapse of mitochondrial membrane potential, lysosomal injury, lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…For example, and similar to studies of inflammatory bowel disease (IBD) (Morgan et al, 2012; Fazlollahi et al, 2018), the induction of β-alanine and butanoate metabolism and bacterial motility and secretion in MET calves indicated a healthier status. Similarly, the upregulation of caprolactam and xylene degradation in the MET group revealed by PICRUSt functional analysis underscores the greater capacity of the microbiota to remove toxic caprolactam and xylene compounds from the hindgut (Hanson et al, 2016; Salimi et al, 2017). The suppression of glutamate and pterine pathways in MET newborns provides additional evidence of a healthier state in MET calves because previous studies reported that glutamate and pterine decreased in healthy humans compared with diseased counterparts with IBD, phenylketonuria and alcoholic liver cirrhosis (Pinheiro de Oliveira et al, 2016; Kolho et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…For example, and similar to studies of inflammatory bowel disease (IBD) (Morgan et al, 2012; Fazlollahi et al, 2018), the induction of β-alanine and butanoate metabolism and bacterial motility and secretion in MET calves indicated a healthier status. Similarly, the upregulation of caprolactam and xylene degradation in the MET group revealed by PICRUSt functional analysis underscores the greater capacity of the microbiota to remove toxic caprolactam and xylene compounds from the hindgut (Hanson et al, 2016; Salimi et al, 2017). The suppression of glutamate and pterine pathways in MET newborns provides additional evidence of a healthier state in MET calves because previous studies reported that glutamate and pterine decreased in healthy humans compared with diseased counterparts with IBD, phenylketonuria and alcoholic liver cirrhosis (Pinheiro de Oliveira et al, 2016; Kolho et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…The mixture was boiled at 95°C for 15 minutes and quickly cooled on ice. The tubes were centrifuged again 10 000 × g for 5 minutes, and the optical density of supernatant measured at 532 nm 25 …”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded into a 24-well plate at a density of 1.0×10 5 cells/ml, treated with 0, 0.625, 1.25, 2.5, 5, or 10 µM shikonin, and maintained at 37°C for 48 h. MTT solution was added to each well and after further incubation for 4 h, the absorbance at 540 nm was determined (Salimi et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%